Assessing Mandated Credit Programs: Case Study of the Magna Carta in the Philippines - Niny Khor; Ryan Jacildo; Ruth Tacneng (Asian Development Bank (ADB), 2015)
We examine the effects of a mandated credit program to small and medium enterprises in the Philippines (Magna Carta Law) using a panel dataset compiled from official data published by the Bangko Sentral ng Pilipinas. The final sample of 109 financial institutions represented over 90% of total finance sector assets in the Philippines. We highlight three important findings. First, although the total lending levels to micro, small, and medium enterprises (MSMEs) grew slightly, the percentage shares of loans allocated to MSMEs declined drastically from a peak of 30% of total loans in 2002 to 16.4% in 2010. Second, following the upwards revision of the loan target (from 6% to 8%) for smaller firms in 2008, there was a sharp increase in noncompliance especially amongst universal and commercial banks. Kernel density estimates suggest that the revision of the Magna Carta in 2008 was binding for small firm lending particularly for the universal and commercial banks. On the other hand, total loans to medium enterprises were still more than threefold larger than the targeted 2%. Third, there is an increased heterogeneity in optimal loan portfolio across banks. Most surprisingly, the absolute level of MSME lending by rural and cooperative banks declined since 2008. Direct compliance amongst universal and commercial banks decreased beginning in the late 2007, while that of thrift banks increased to almost 100%. Abolishing the Magna Carta targets for medium-sized enterprise loans would most likely yield little adverse effects. Meanwhile, efforts to improve financial access to MSMEs should focus on alternative nondistortionary ways to increase financing supply, such as improving institutional framework for informational availability and development of equity and bond markets for MSMEs.
hdl:11540/5270
Keywords: G21; G28; O16; 330; financial inclusion; financial markets; financial policy; Philippines; SME; targeted lending